Regulation of axon pathfinding by astroglia across genetic model organisms - Rapti, Georgia (Frontiers in Cellular Neuroscience, 2023)
Glia and neurons are intimately associated throughout bilaterian nervous systems and were early proposed to interact for patterning circuit assembly. The investigations of circuit formation progressed from early hypotheses of intermediate guideposts and a "glia blueprint" to recent genetic and cell manipulations, and visualizations in vivo. An array of molecular factors are implicated in axon pathfinding but their number appears small relatively to circuit complexity. Comprehending this circuit complexity requires to identify unknown factors and dissect molecular topographies. Glia contribute to both aspects and certain studies provide molecular and functional insights into these contributions. Here, I survey glial roles in guiding axon navigation in vivo, emphasizing analogies, differences and open questions across major genetic models. I highlight studies pioneering the topic, and dissect recent findings that further advance our current molecular understanding. Circuits of the vertebrate forebrain, visual system and neural tube in zebrafish, mouse and chick, the Drosophila ventral cord and the C. elegans brain-like neuropil emerge as major contexts to study glial cell functions in axon navigation. I present astroglial cell types in these models, and their molecular and cellular interactions that drive axon guidance. I underline shared principles across models, conceptual or technical complications, and open questions that await investigation. Glia of the radialastrocyte lineage, emerge as regulators of axon pathfinding, often employing common molecular factors across models. Yet this survey also highlights different involvements of glia in embryonic navigation or pioneer axon pathfinding, and unknowns in the molecular underpinnings of glial cell functions. Future cellular and molecular investigations should complete the comprehensive view of glial roles in circuit assembly.